El MGIE, un modelo de gestión energética para el sector productivo nacional (2008)
This paper present a mo¬del of energy management for colombian productive sector, denominated Modelo de Gestión Integral de la Energía (MGIE). This model has been developed considering national and inter¬national experiences in energy management in the last 15 years, the state of development of the national productive sector has be considering. The application of the MGIE, allows to install in the company the Sistema de gestión integral de la energía (SGIE) and to reduce the power consumption and the costs of the energy. The final object of the MGIE is that the company to obtained an environmental energy culture that allow the increase of the productivity or the com¬petitiveness and the reduction of the environmental impact in a vision of sustainable energy development.